2007
DOI: 10.1002/mpr.217
|View full text |Cite
|
Sign up to set email alerts
|

A dimensional approach to developmental psychopathology

Abstract: The expression psychopathology in general and child psychopathology in particular, is affected by multiple sources of variance. Some of these sources include gender differences, informant differences, and age-related differences. In this paper, we discuss how these sources of variance complicate both research and clinical management. We argue that the current diagnostic system would be aided by the inclusion of a quantitative axis that can take these sources of variance into account. We reason that the fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
196
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(209 citation statements)
references
References 31 publications
9
196
0
4
Order By: Relevance
“…Como desfechos possíveis do processo de desenvolvimento 12 , os transtornos mentais não seriam necessariamente categorias distintas, mas sim trajetórias desenvolvimentais dimensionais 10 . Como uma complexa malha rodoviária, em que diferentes rodovias podem levar ao mesmo local, diferentes trajetórias desenvolvimentais podem levar ao mesmo processo psicopatológico.…”
Section: Quais São Os Conceitos E Abordagens Desenvolvimentais Que Nounclassified
See 1 more Smart Citation
“…Como desfechos possíveis do processo de desenvolvimento 12 , os transtornos mentais não seriam necessariamente categorias distintas, mas sim trajetórias desenvolvimentais dimensionais 10 . Como uma complexa malha rodoviária, em que diferentes rodovias podem levar ao mesmo local, diferentes trajetórias desenvolvimentais podem levar ao mesmo processo psicopatológico.…”
Section: Quais São Os Conceitos E Abordagens Desenvolvimentais Que Nounclassified
“…Neste artigo, são discutidos conceitos e abordagens utilizados por esse modelo para compreender como e por que determinados in di víduos desenvolvem transtornos mentais. Inúmeros artigos de revisão sobre diferentes aspectos dessa disciplina [2][3][4][10][11][12][13] foram publicados, assim como um livro texto com mais de 3.000 páginas 14 . Portanto, o objetivo deste artigo é esti mu lar que o leitor considere esta abordagem na sua busca indi vidual por ferramentas para entender o processo de desen volvimento dos transtornos mentais.…”
Section: Introductionunclassified
“…The co-occurrence of comorbid disorders -both internalizing (e.g., anxiety and depression) and externalizing (e.g., aggressive and delinquent behaviors) -with ADHD is a consistently replicated finding (Baeyens, Roeyers & Walle, 2006;Milich, Balentine & Lynam, 2001). Previous studies shown that it is important to look for higher-order patterns among symptoms of different disorders (Hudziak, Althoff, Derks, Faraone, & Boomsma, 2005;Hudziak, Achenbach, Althoff & Spine, 2007;Stevenson et al, 2005). Mechanisms underlying various constellations of psychopathological symptoms may differ (Hudziak et al, 2005(Hudziak et al, , 2007Stevenson et al, 2005).…”
mentioning
confidence: 99%
“…Previous studies shown that it is important to look for higher-order patterns among symptoms of different disorders (Hudziak, Althoff, Derks, Faraone, & Boomsma, 2005;Hudziak, Achenbach, Althoff & Spine, 2007;Stevenson et al, 2005). Mechanisms underlying various constellations of psychopathological symptoms may differ (Hudziak et al, 2005(Hudziak et al, , 2007Stevenson et al, 2005). For example, a study performed by Hudziak and colleges (2005) shows that children with comorbid ADHD, ODD and MDD are characterized by distinct genetic factors compared to children with different configurations of these psychopathological symptoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation